Improved Integrated Thematic Learning Outcomes Applying Immersed Models For Elementary School - Nur Atikah; Santia Indah Purnama; Afriya Mahdalena; Risda Amini (STAI Miftahul Ula Nganjuk, 2021)
The purpose of this study is to describe the learning outcomes of grade 3 elementary students through immersed model. This research was conducted in the even semester of teachings 2019/2020. The research method used is Class Action Research (PTK) with 3 cycles of action. The subjects of the study were grade 3 students, totaling 28 students, consisting of 14 male learners and 14 female learners. The data collection technique used is test. The test was conducted to measure the level of completion of learners' learning outcomes in learning through immersed model models. In the implementation of research through immersed models through the stages of planning, implementation, observation, and reflection. From the results of the study on cycle I obtained a percentage of classical completion 55.17%. In cycle II there was an increase in classical completion learning outcomes of 82.76%. It can be concluded that the model of make a match and media diorama can improve the learning outcomes of grade 3 elementary students